2019
DOI: 10.1177/1362361318809690
|View full text |Cite
|
Sign up to set email alerts
|

Autism severity, co-occurring psychopathology, and intellectual functioning predict supportive school services for youth with autism spectrum disorder

Abstract: Supportive school services are a primary service modality for youth with autism spectrum disorder. Autism spectrum disorder, as well as co-occurring psychiatric symptoms and low intellectual abilities, interfere with academic achievement and therefore influence decisions about school services. Therefore, we examined the association of parent, teacher, and clinician ratings of autism spectrum disorder and co-occurring psychiatric symptom severity and intellectual functioning with school services. In total, 283 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…To date, only a few studies have examined psychiatric symptoms on the delivery of school-based services for youth with ASD. For example, co-occurring ADHD in youth with ASD either does not predict school-based services despite associations with a greater need for services (Narendorf, Shattuck, & Sterzing, 2011) or higher parent-rated externalizing symptoms predict lower likelihood of receiving school-based services (Rosen, Spaulding, Gates, & Lerner, 2019). This is in contrast to the current study, in which higher teacher-rated ADHD symptoms predicted higher rates of receiving special education.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have examined psychiatric symptoms on the delivery of school-based services for youth with ASD. For example, co-occurring ADHD in youth with ASD either does not predict school-based services despite associations with a greater need for services (Narendorf, Shattuck, & Sterzing, 2011) or higher parent-rated externalizing symptoms predict lower likelihood of receiving school-based services (Rosen, Spaulding, Gates, & Lerner, 2019). This is in contrast to the current study, in which higher teacher-rated ADHD symptoms predicted higher rates of receiving special education.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similar research also focused on ASD severity, co-occurring psychopathology, and intellectual functioning predicting supportive school services for youth with ASD. 33 This research discussed how greater ASD symptom severity necessitates more intensive and frequent school supports, in addition to ASD severity, co-occurring psychiatric symptoms and low intellectual functioning may also interfere with a student's academic progress. 33…”
Section: Comorbid Psychopathology and Asd Severitymentioning
confidence: 99%
“…33 This research discussed how greater ASD symptom severity necessitates more intensive and frequent school supports, in addition to ASD severity, co-occurring psychiatric symptoms and low intellectual functioning may also interfere with a student's academic progress. 33…”
Section: Comorbid Psychopathology and Asd Severitymentioning
confidence: 99%
“…One study of a nationally representative sample found that over 80% of students served under autism eligibility in the school received services that were directly related to core autism‐related impairment (i.e., language and speech, occupational therapy, and behavior management services) (Wei et al, 2014). Studies including clinic‐referred samples have also reported language and speech and occupational therapy to be common school‐based special education services received by autistic students, however, sample acquisition and sociodemographic characteristics of the samples limit the generalizability of these findings to more diverse groups of students (McDonald et al, 2019; Rosen et al, 2019; Spaulding et al, 2017). The quantity and types of services received in schools by autistic students from underserved groups have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%